(untitled) (CIPEEX, 2025)
University extension projects represent an opportunity to integrate teaching and community engagement, enabling the promotion of health in a playful and participatory way. In socially vulnerable contexts, educational activities associated with food donation can contribute to nutritional awareness, autonomy, and the strengthening of community bonds. This study reports the experience of a food fair held in a low-income community as part of a university extension project, aiming to promote health education, financial education, autonomy, and social responsibility among children. Activities were carried out weekly, on Fridays, with children from the community, addressing topics such as dengue prevention, first aid, personal hygiene, and financial education. At each meeting, children received toy coins as a reward for participation, accumulating values that were later used in a simulated food fair. The products offered—fruits, vegetables, and non-perishable foods—were collected through a solidarity campaign organized by the Student Directory of the Medicine course at UniEVANGÉLICA. At the fair, children were able to use the accumulated coins to “purchase” the foods of their choice and assemble a basket to take home. This dynamic, in addition to fostering active participation and playful engagement, stimulated notions of resource management, autonomy, and appreciation of personal choices. Strong interaction and gratitude were observed among the children, as well as direct benefits to their families through food donations. The experience demonstrated that the food fair, as a university extension activity, is an effective strategy to integrate health education, financial education, and social responsibility, strengthening the bond between university and community and contributing to the comprehensive training of medical students.